2007
DOI: 10.1593/neo.07673
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase Levels Are Elevated in the Plasma of Pediatric Cancer Patients and Correlate with Response to Anticancer Treatment

Abstract: Heparanase is an endoglycosidase that specifically cleaves heparan sulfate (HS) side chains of heparan sulfate proteoglycans, the major proteoglycan in the extracellular matrix (ECM) and cell surfaces. Heparanase upregulation was documented in an increasing number of primary human tumors, correlating with reduced postoperative survival rate and enhanced tumor angiogenesis. The purpose of the current study was to determine heparanase levels in blood samples collected from pediatric cancer patients using an ELIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…The occurrence of active heparanase extracellularly is further supported by the establishment of an ELISA method which preferentially recognizes the active 50 kDa enzyme vs. the latent 65 kDa protein [114]. Applying this method it was demonstrated that heparanase levels are elevated in the plasma of pediatric cancer patients, correlating with their response to anti-cancer treatments [115]. Likewise, elevated levels of heparanase were measured in the urine of bladder cancer patients, associating with disease progression [116].…”
Section: Post-transcriptional Regulation Biosynthesis Trafficking mentioning
confidence: 99%
“…The occurrence of active heparanase extracellularly is further supported by the establishment of an ELISA method which preferentially recognizes the active 50 kDa enzyme vs. the latent 65 kDa protein [114]. Applying this method it was demonstrated that heparanase levels are elevated in the plasma of pediatric cancer patients, correlating with their response to anti-cancer treatments [115]. Likewise, elevated levels of heparanase were measured in the urine of bladder cancer patients, associating with disease progression [116].…”
Section: Post-transcriptional Regulation Biosynthesis Trafficking mentioning
confidence: 99%
“…Using an ELISA method, 21 it was found that the level of active heparanase (GS3 8+50 kDa) in plasma drawn in sodium citrate was 500±29 pg/mL (0.0085 μM). 22 When heparanase, factor VIIa and factor X were incubated (15 min, 37°C) with pooled normal human plasma from five healthy donors, followed by the addition of a chromogenic substrate for factor Xa, a 7-to 8-fold increase in factor Xa levels was obtained compared to levels in plasma incubated in the absence of heparanase (Figure 2). In this condition the coagulation was mainly dependent on the concentration of endogenous TF, as described previously.…”
Section: Heparanase In Human Plasmamentioning
confidence: 99%
“…Heparanase upregulation was noted in an increasing number of primary human cancers, correlating with reduced postoperative survival of cancer patients (5,9). Elevated levels of heparanase were detected in the urine and plasma of patients with aggressive metastatic disease (11). Recently, we cloned a splice variant of human heparanase lacking exon 5 whose function has yet to be unraveled (12).…”
mentioning
confidence: 99%